Platformization of cultural production and crowdfunding: Co-creation dynamics and the multiple roles of digital platforms shaping the Portuguese cultural crowdfunding ecosystem - Foá, C. (Arts and humanities in digital transition: Book of abstracts, 2023)
Abstract. The dynamics of platformisation of society and cultural production (Van Dijck, 2020; Nieborg et al., 2019; Serazio et al., 2019) cross the disruption of creative value chains, the growing contingency of cultural products and the emergence of new professionals and roles. The reformulation of cultural products’ meaning, and its disappearance (Bilton, 2017) relate to agents’ structure and power negotiation forces, and their options for building collaborative, competitive or coopetitive relations (Gandini e Graham, 2017), to create, produce, fund, and disseminate works of art. GAFAM and global production and promotional industries lay on for profit data-driven processes, distribution operation and interactions “algorithmically turned” (Nieborg e Poell, 2018; Napoli, 2014), influencing digital marketing strategies of smaller agents. The study characterizes the Portuguese cultural crowdfunding ecosystem, composed by agents featured by roles, strategies, and experiences (Lehner e Harrer, 2019; Quero and Ventura, 2019), discussing the influence of platformization and social media dominance on collaborative processes.